Total Assets and Audit Opinion: Impact on Audit Delay in Food and Beverage Manufacturing: Pengaruh Total Aset dan Opini Audit terhadap Penundaan Audit pada Perusahaan Manufaktur Subsektor Makanan dan Minuman: Bukti dari Bursa Efek Indonesia - Akhmad Zain Muzauwas; Nurasik Nurasik (Academia Open, 2023)
This research aims to investigate the effect of Total Assets, Profitability, Solvency, and Audit Opinion on Audit Delay in the Food and Beverage Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange during the period of 2018-2020. The study utilized secondary data from financial statements and annual reports obtained from the website of Bursa Efek Indonesia. The sample comprised 24 purposively selected companies, representing a three-year observation period. Descriptive statistical analysis, classic assumption tests, t-tests, and multiple regression analysis using SPSS version 20 software were conducted for data analysis. The findings reveal that Total Assets and Audit Opinion exerted a significant negative influence on audit delay. However, Profitability and Solvency were found to have no significant effect on audit delay. These results contribute to the understanding of factors affecting audit delay in the food and beverage manufacturing sector and have implications for auditors, regulators, and researchers in the field of financial auditing. Highlights: The study examines the impact of Total Assets and Audit Opinion on Audit Delay in the Food and Beverage Manufacturing companies listed on the Indonesia Stock Exchange. Findings reveal that Total Assets and Audit Opinion have a significant negative effect on Audit Delay. This research contributes to understanding the factors influencing Audit Delay in the food and beverage manufacturing sector and has implications for auditors, regulators, and researchers in the field of financial auditing. Keywords: Total Assets, Audit Opinion, Audit Delay, Food and Beverage Manufacturing, Indonesia Stock Exchange.